Quantitative wear evaluation of tips based on sharp structures - Xu, Ke; Leng, Houwen (Beilstein Journal of Nanotechnology, 2024)
To comprehensively study the influence of atomic force microscopy (AFM) scanning parameters on tip wear, a tip wear assessment method based on sharp structures is proposed. This research explored the wear of AFM tips during tapping mode and examined the effects of scanning parameters on estimated tip diameter and surface roughness. The experiment results show that the non-destructive method for measuring tip morphology is highly repeatable. Additionally, a set of principles for optimizing scanning parameters has been proposed. These principles consider both scanning precision and tip wear. To achieve these results, an AFM probe was used to scan sharp structures, precisely acquiring the tip morphology. Tip wear was minimized by employing lower scanning frequency and free amplitude, and a set point of approximately 0.2, resulting in clear, high-quality AFM images.
Keywords: atomic force microscopy; estimated tip diameter; scanning parameter; tip reconstruction; tip wear